Hazard Identification Using Task Risk Assessment Method and Bowtie Analysis (Case Study: PT. Varia Usaha Beton) - Setianingsih, Dika; Hasyim Asyari (TALENTA Publisher, 2024)
PT. Varia Usaha Beton is a subsidiary of PT. Semen Indonesia Beton, which produces various types of products. PT Varia Usaha Beton (BSP Purwokerto) has an open work area where there are potential hazards such as physical factors, chemical factors and ergonomic factors. The aim of this research is to identify hazards, assess risks and control risks in the production process of ready-mixed concrete so that workplace accidents can be minimized. The methods used in this research are task risk assessment and bowtie analysis. Based on the research results, it was found that 1 risk belonged to the low category, 27 risks belonged to the medium category, and 11 risks belonged to the high category. Based on the bow-tie method, the major risks are exposure to fly ash and cement dust, risk of diesel spills, and risk of electric shock. The main causes of workplace accidents are pipe leaks and improper diesel filling. The main risk effects of workplace accidents are worker injury, and fire. The bowtie analysis method determines that the risk of electric shock is due to a damaged cable and the existing protective barrier is intended to replace the damaged cable. This risk has consequences, namely injuries to workers.